La Extremadura cristiana (1142-1230): ocupación del espacio y transformaciones socioeconómicas. - Montaña Conchiña, Juan Luis de la; Clemente Ramos, Julian (Historia. Instituciones. Documentos, 2018)
RESUMEN: ABSTRACT: